2011, a great year for virtual libraries - Agenjo, Xavier (Anuario ThinkEPI, 2012)
The Europeana project progress is presented, emphasizing its importance among other strategies of the European Commission. In 2011 important recommendations and standards were published that clarify the future development of Europeana. Documents produced by the W3C are highlighted and Spanish contributions, particularly from Hispana, are listed. The collaboration between Europeana and the Digital Public Library of America is mentioned. Finally, the differences between various concepts like open access, open data and open source are explained.